Enhancing shelf life of Trichoderma harzianum by conidial storage in sterile deionized water - M Anandaraj, R Suseela Bhai, (Journal of Spices and Aromatic Crops, 2014)
In this study T. harzianum conidial suspension was made in different concentrations of cryoprotectants viz., glycerol, glucose, DMSO and deionized distilled water and stored at two different temperatures viz., 25± 1oC and 28-32ºC for more than 720 days for evaluating the shelf life in order to develop a ready to use liquid carrier formulation. The results showed that submerged conidia formulation in cryoprotectants like glycerol, glucose and DMSO preserved the viability for 75 days only when compared to the formulation in sterile deionized water which at 28-32°C retained the viability for 480 days with a viable count of loge= 6.671 (3.2 × 106) and for more than 720 days with a viable count of loge=5.54 (2 × 105) and in 480 days at 25±1°C with a viable count of loge=6.3911 (6.5 × 106) and with a viable count of loge =5.40 (2 × 105) for more than 720 days. The viability was tested in vitro by recovery in TSM and effectiveness was tested in vivo by drenching the suspension on plants and challenge inoculating with Phytophthora capsici after seven days. Challenge inoculation of black pepper plants with P. capsici after drenching with diluted stored suspension gave a disease reduction of 66.67%. Hence, sterile deionized water can be used as a liquid storage medium for the long term storage of T. harzianum culture without loosing the viability and effectiveness of the spores.